Pengaruh Peningkatan Kekuatan Iran Terhadap Hegemoni Amerika Serikat di Timur Tengah - Ramadhan, Reza Bakhtiar (Universitas Islam Negeri Raden Intan Lampung, 2019)
Using the method of discourse analysis and the theory of Balance of Power as a media for analysis of this paper seeks to find out why and how the increase in Iranian military power threatens the hegemony of the United States in the Middle East. Significant increases in Iranian military power are thought to threaten US interests in the Middle East. Post-revolution of Iran under the leadership of Ayatollah Khomeini in 1979 has turned this country into a new political and military power. Since then, relations between Iran and the West, especially the United States, are becoming more tense. Iran's policy on nuclear weapons has triggered an arm of race in the Middle East. Even Iran is considered to threaten the stability of the region's security. Especially the security of the United States allies in the Middle East. Saudi Arabia emerged as one of Iran's main opponents in the Middle East region. One vote with a colleague of the United States, the Saudis have always denounced all Iranian political and military policies. Given the enormous importance of the United States in the Middle East, as well as its responsibilities to the security of its allies in the Middle East, various ways in which the United States has secured its hegemony. Like strengthening alliances with its Middle East allies by way of massive military supply of weapons.